A general formula for the uniform flow of water in rivers and other channels - Ganguillet, E. (Chapman & Hall, 1907)
Part 1 deals with general remarks, historical matter, latest (at the time) researches and their results and part 2 covers the main topic of the formula for the flow of water in rivers and other channels. There are 9 appendices.